Durability Behavior of Self Compacting Concrete Made with Recycled Concrete Aggregate - V. Arul Prakash, T.; M. Natarajan, Dr.; T. Senthil Vadivel, Dr.; V.Karthik, Dr.; ., . (International Journal of Engineering and Technology, 2018)
This article presents the influence of the Recycled Concrete Aggregate (RCA) on the durability behavior of self-compacting fly ash concrete (M30 Grade). The RCA from local construction demolition site wereemployed as a replacement for natural coarse aggregate (0% - 30%) in self-compacting concrete(SCC). The Viscosity modifying material used in this study was Class F fly ash. Different kinds of tests were conducted on the concrete specimens such as water absorption test, sulphate attack, chloride attack, carbonation test,sorptivity test, etc., When the durability behavior was taken into consideration,the summary of results indicate that recycled concrete aggregate different percentage of replacements as the optimal percentagein the manufacture of SCC without much affecting strength and durability.Â